Understanding the element of undue influence that may render a contract voidable - Che Rose, Sarirah; Kamarudin, Irma; Abdullah Sanek, Siti Khadijah (Universiti Teknologi MARA, Kedah, 2025)
An agreement becomes a contract when the contracting parties have free consent and are competent to enter into a contract. This is provided for under section 10 of the Contract Act 1950 (hereinafter referred to as ‘the Act’). According to section 14 of the Act, consent is free when it is not caused by coercion, fraud, misrepresentation, undue influence or mistake. The elements of coercion, fraud, misrepresentation, and undue influence may render a contract voidable while a mistake may render a contract void.